Impact of Tick Size Reduction on Small Caps Price Efficiency and Execution Cost on the Indonesia Stock Exchange - Irwan Adi Ekaputra,; Erni Sukmadini Asikin, (Asian Academy of Management Journal of Accounting and Finance, 2012)
On 2 January 2007, the Indonesia Stock Exchange (IDX) implements a new tick size of Rp1 in addition to the extant Rp5, Rp10, Rp25 and Rp50 tick sizes. This research investigates the impact of tick size reduction on stock price efficiency and execution cost. The microstructure effect of the new tick size should only impact small caps traded at Rp200 or lower, for those shares were previously traded at Rp5 tick. Using OLS and quantile regressions, we find the new tick policy significantly improves small caps price efficiency and partially reduces execution cost. The new tick size moderately reduces the mean of execution cost but does not reduce the median.